غلام عباس کے افسانوں میں شہری زندگی کی پیش کش "اوور کوٹ "اور "کتبہ" کی روشنی میں (تجزیاتی مطالعہ): Presentation of urban life in Ghulam Abbas's fiction In the Light of "Overcoat" and "Katbah" (Analytical Study) (Khairulummah, 2022)
Every man of letters has his or her own narrative world, or distinct circle. It may be so broad or limited; but this does not matter as success of the author draws on his or her talent and skill in presenting his or her art within this circle. This should be attained meticulously. Regarding Gholam Abbas, he had relied on his own local environment while choosing his world of narration. His circle revolves within the city of Lahore in which he grew up witnessing its joys, sorrows, victories, and setbacks. With outstanding skill, he depicted its problems and cares of its people. Out of this local milieu, he attained worldwide fame through extreme locality. In this respect, he resembles the Egyptian Naguib Mahfouz, whose stories and novels took place inside the city of Cairo. The most prominent element in the stories of Gholam Abbas is shedding light on the city’s cruelty to its people, especially the working class who show contrary to what they hide and try to coexist with that painful reality. This is evident through “Over coat” and “kataba” story. His stories also highlight the image of city life, crowds, high-rise buildings, buying and selling in the city hub, the image of street vendors over bridges, traffic and its jamming during rush hours of employees. The psychological state experienced by the residents of the city is depicted, too. Also handled are the crowded city and the psychological pressures on the simple employees, and the class disparity among the people of the city, where the poor aspire to live on a level close to the rich of the city, but no way.. never.